A Radiographic Abdominal Pannus Sign is Associated With Postoperative Complications in Anterior THA. Issue 5 (11th May 2023) - Saini, Atul; Dbeis, Ammer; Bascom, Nathan; Sanderson, Brent; Golden, Thomas
Abstract: Background: Numerous studies have shown that elevated BMI is associated with adverse outcomes in THA; however, BMI alone does not adequately represent a patient's adipose and soft tissue distribution, especially when the direct-anterior approach is evaluated. Local soft tissue and adipose, especially in the peri-incisional region, has an unknown impact on patient outcomes after direct-anterior THA. Moreover, there is currently no known evaluation method to estimate the quantity of local soft tissue and adipose tissue. The current study introduced a new radiographic parameter that is measurable on supine AP radiographs: the abdominal pannus sign. Question/purpose: Are patients who have an abdominal pannus extending below the upper (cephalad) border of the symphysis pubis more likely to experience problems after anterior-approach THA that are plausibly associated with that finding, including infections resulting in readmission, wound complications resulting in readmission, fractures, or longer surgical time, than patients who do not demonstrate this radiographic sign? Methods: Between 2015 and 2020, five surgeons performed 727 primary direct-anterior THAs. After exclusion criteria were applied, 596 procedures were included. Of those, we obtained postoperative radiographs in the postanesthesia care unit in 100% of procedures (596 of 596), and 100% of radiographs (596) were adequate for review in this retrospective study. The level of the pannus in relation to the pubic symphysis was assessed on immediate supine postoperative AP radiographs of the pelvis: above (pannus sign 1), between the upper and lower borders (pannus sign 2), or below the level of the pubic symphysis (pannus sign 3). In this study, we combined pannus signs 2 and 3 into a single group for analysis not only because there was a limited number of patients in each group, but also because there was no statistically significant difference between the two groups. Pannus sign 1 was identified in 82% of procedures (486 of 596), and pannus sign ≥ 2 was identified in 18% (110). We compared the groups (pannus sign 1 versus pannus sign ≥ 2) in terms of the percentage of patients who experienced problems within 90 days of THA that might be associated with that physical finding, including infections resulting in readmission including subcutaneous, subfascial, and prosthetic joint infections; wound complications resulting in readmission, defined as dehiscence or delayed healing; and all fractures, and we compared the groups in terms of surgical time—that is, the cut-to-close time. Results: Patients with a pannus sign of ≥ 2 were more likely than those with a pannus sign of 1 to have a postoperative infection (6.4% [seven of 110 procedures] versus 0.6% [three of 486], odds ratio 10.96 [95% confidence interval (CI) 2.83 to 42.38]; p < 0.01), wound complications (0.9% [one of 110] versus 0% [0 of 486] with an infinite odds ratio [95% CI indeterminate]; p = 0.18), and fractures (4.5% [five of 110] versus 0% [0 of 486], with an infinite odds ratio [95% CI indeterminate]; p < 0.01). The mean surgical time was longer in patients with a pannus sign of ≥ 2 than it was in those with a pannus sign of 1 (128 ± 25.3 minutes versus 118 ± 27.5 minutes, mean difference 10 minutes; p < 0.01). Conclusion: Based on these findings, patients who have an abdominal pannus that extends below the upper (cephalad) edge of the pubic symphysis are at an increased risk of experiencing serious surgical complications. If THA is planned in these patients, an approach other than the direct-anterior approach should be considered. Surgeons performing THA who do not obtain supine radiographs preoperatively should use a physical examination to evaluate for this finding, and if it is present, they should use an approach other than the direct-anterior approach to minimize the risk of these complications. Future studies might compare the abdominal pannus sign using standing radiographs, which are used more often, with other well-documented associated risk factors such as elevated BMI or higher American Society of Anesthesiologists classification. Level of Evidence: Level III, retrospective cohort study.